Tecnología y procesamiento de especies maderables y su relación con la contaminación ambiental en dos plantas de transformación primaria en Iquitos 2017 - Morey Flores, Luis Alberto (2024)
The work was developed in Iquitos in two plants of wooden transformation, the purpose was of determining if the transformation process and prosecution cause environmental contamination, the universe was conformed for (70 people) that work in both companies, the qualitative, prospective design was used since he/she didn't modify any fact, which were processed in Excel and represented in chart and graphic, being reached the following conclusions: Environmental contamination exists in the process of transformation of the wood in both companies, for what is suggested: To implement more efficient and more sustainable technologies, to minimize the contamination; the improvement of the productive processes can have a positive impact in the atmosphere. The main polluting sources are the emissions of particles (powder), sawdust, chip and liquids that are generated during the transformation, to implement practical of cleaner and more sustainable production, as the reutilization and recycle of materials, which can help to reduce the quantity of generated residuals. To carry out regular monitored of the contamination and generated quantity of residuals, to identify areas of improvements and to evaluate the effectiveness of the implemented measures. To implement training chats for the personnel in cleaner and more sustainable productions, to assure the effective implementation of technologies and more efficient processes in the company.